Pemanfaatan Doula Labour Coach Application Untuk Membantu Relaksasi Ibu Pada Persalinan Kala 1 - Hasriani Saleng; Dwi Ghita (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
In the delivery process, family assistance through the active role of family members by bringing loved ones to the birth process can provide physical and psychological support to the mother which can create a feeling of security and comfort for the mother. Support from the husband is a form of family support that has the greatest impact on the mother's behavior in the delivery process. This community service activity is carried out by providing counseling to pregnant women who are in the Muzzle Bulu Village area, Maros Regency. The purpose of this activity is to educate pregnant women about the importance of assistance in the delivery process, support for childbirth assistance, the importance of assistance in the delivery process, the benefits of the importance of assistance in the delivery process. The knowledge of pregnant women related to the use of the Doula labor coach application to help relax the mother in the 1st stage of labor has increased significantly. Doulas are able to balance the patient's emotions and can provide positive support to face labor calmly and comfortably. Counseling Program Regarding the benefits of the importance of assistance during childbirth carried out well and running smoothly according to the activity plan that has been prepared, without significant obstacles accompanied by the enthusiasm of the participants in participating.